The Influence of Profit Sharing Financing, Murabaha Financing, Non-Performing Financing, Inflation and Exchange Rates on Profitability of Sharia Commercial Banks in Indonesia - Rita Rosiana; Syihabudin Syihabudin; Siti Nurmeilani (FEB Universitas Sultan Ageng Tirtayasa, 2019)
The purpose of this study is to examine the effect of profit sharing financing, murabaha financing, non-performing financing (NPF), inflation and exchange rates on the profitability of sharia commercial banks in Indonesia. The data used are secondary data in the form of Islamic Commercial Bank financial statements and exchange rate data and inflation data obtained from the websites of each Sharia Commercial Bank and Bank Indonesia. The total data used in this study were 40 samples obtained from 8 Islamic Commercial Banks for a period of 5 years. The results of this study conclude: murabaha financing, inflation and exchange rates do not affect the Profitability of Sharia Commercial Banks in Indonesia. Profit sharing financing and non-performing financing (NPF) negatively affects the profitability of Sharia Commercial Banks in Indonesia.